2022
DOI: 10.3390/cancers14194606
|View full text |Cite
|
Sign up to set email alerts
|

Change of the Neutrophil-to-Lymphocyte Ratio during Treatment: A Potential Prognostic Biomarker in Metastatic Prostate Cancer Treated with Radium-223 Dichloride

Abstract: The neutrophil to lymphocyte ratio (NLR) at baseline has been shown to have prognostic value in metastatic prostate cancer. Little is known about the importance of a change in the NLR during treatment in patients treated with Radium-223 (223Ra). We investigated the prognostic value of the NLR at baseline and during therapy in patients with metastatic prostate cancer treated with 223Ra and also in patients treated with Docetaxel. We reviewed all patients treated with 223Ra in our center and randomly chosen pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…43 In another series analyzing men undergoing treatment with Ra-223 dichloride, OS was significantly longer in individuals that had both an NLR ≤ 5, compared to those treated with docetaxel chemotherapy. 13 Ra-223 dichloride may have a direct effect on the bone marrow due to proximity which may be reflected by the lymphocytes and neutrophil count, which may modulate the host's immune response to cancer through treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43 In another series analyzing men undergoing treatment with Ra-223 dichloride, OS was significantly longer in individuals that had both an NLR ≤ 5, compared to those treated with docetaxel chemotherapy. 13 Ra-223 dichloride may have a direct effect on the bone marrow due to proximity which may be reflected by the lymphocytes and neutrophil count, which may modulate the host's immune response to cancer through treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR is thought to reflect systemic inflammation as well as the host immune response and the tumor microenvironment 10,11 . Independently, the lymphocyte and neutrophil counts depend on many factors and can be influenced by systemic therapy 12–14 . Emerging evidence indicates that a high NLR is associated with a lower PSA response rate after treatment for mCRPC using chemotherapy and androgen synthesis inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggesting the need for further study. [146][147][148][149] Investigating specifically SII in a retrospective multicentre cohort of over 6000 men treated surgically for localised PCa, elevated presurgical SII was found to be significantly associated with both adverse surgical pathology and longer term BCR. 150 The predictive value of the SII is supported by other studies in localised PCa post surgery examining not only BCR but also long term survival.…”
Section: Diet Onlymentioning
confidence: 99%
“…A retrospective study from Japan on 633 men before PCa diagnosis found, by contrast, low NLR and PLR were predictive of finding PCa at subsequent biopsy 145 . In other studies, the accuracy of NLR as a prognostic marker of disease progression in localised PCa or response to treatment (e.g., docetaxel, cabazitaxel or radium‐223) in advanced PCa has been inconclusive suggesting the need for further study 146–149 …”
Section: Specific Effect Of Lifestyle Interventions On Biomarkers Met...mentioning
confidence: 99%